Sosialisasi Stimulasi Kreativitas Dalam Membangun Umkm - Jiddan, Brilian Ghol; Rani, Aullya Bintang Puspa; Khoirunnisa, Nazla; Khairunisya, Naila; Rivandi, Ivan; Puspitasari, Denisa; Muchid, Tegar; Permana, Faris Naufal; Ardhana, Dizky Henrico; Pertiwi, Aisyah Amelia; Susila, Muh. Endrio (Prosiding Seminar Nasional Program Pengabdian Masyarakat, 2024)
UMKM are one of the backbones of the local economy. They often play a role in meeting the daily needs of local residents and can also be a source of income for residents of the hamlet. UMKM in the hamlet can be of various types, ranging from farming businesses such as small-scale agriculture and animal husbandry, home industries such as handicrafts, local food production, to services such as repairmen or the provision of local transportation services. This research aims to increase the understanding of the community, especially those who do not have the motivation to build a business and develop community creativity, especially ideas that have not been created in building Micro, Small and Medium Enterprises (UMKM) in Padukuhan Plono Timur. The process of developing this creativity is carried out through the Community Service Program (KKN) of Muhammadiyah University of Yogyakarta (UMY) in Padukuhan Plono Timur, Pagerharjo Village, Samigaluh District, Kulon Progo Regency, Yogyakarta Special Region. This research uses a qualitative approach by collecting data through interviews, observations. Research conducted by KKN UMY regarding the work program, namely “Stimulating Creativity in Building UMKM”. The results of this study show that the UMY KKN Work Program has an important role in finding solutions to the lack of motivation and creativity of the people of Padukuhan Plono Timur by combining educational, participatory, and collaborative approaches. Through a socialization, this program contributes to improving people's understanding of the importance of motivation and creativity of ideas in building a business. This research can provide insights that increase Natural Resources (SDA) and Human Resources (HR) regarding the importance of increasing creativity in business so that it can help the community in building ideas in a business in Padukuhan Plono Timur.